The Influence of Firm Characteristics and Export Performance in Central and Eastern Europe: Comparisons of Visegrad, Baltic and Caucasus States - Andrzej Cieślik; Jan Michałek; Anna Michałek (Entrepreneurial Business and Economics Review)
In this paper we study the firm-level determinants of export performance in three groups of countries: the Visegrad, Baltic and Caucasus countries. Our analytical framework refers to the most recent strand in the new trade theory literature based on the Melitz (2003) model that stresses the importance of firm productivity in entering the export markets. The empirical implementation of the theoretical framework is based on the probit model and the BEEPS data set. Our empirical results confirm the importance of firm characteristics for export performance in the CEE countries. Also heterogeneity between different country groups within the region has been reported. Export competitiveness of firms from the CEE countries can be improved through the development of modern educational systems allowing to accelerate the accumulation of human capital. The financial support to research and development and innovation activities should also have a positive impact on the export performance of firms from the CEE countries. We take into account labor productivity and other firm characteristics that may affect export performance such as the age and the size of the firm, the use of human capital, and the degree of firm internationalization.